1994
DOI: 10.1557/jmr.1994.1147
|View full text |Cite
|
Sign up to set email alerts
|

Deformation mechanisms of Al films on oxidized Si wafers

Abstract: The mechanism for plastic deformation of 0.5 μm thick, 0.5 μm grain-size evaporated Al films on oxidized Si wafers has been studied using wafer curvature measurements over a temperature range from room temperature to 500 °C. Extensive evidence for both morphology changes and plastic deformation was obtained. Transmission electron microscopy confirmed the occurrence of grain growth, and stress changes attributed to recrystallization were observed. Deformation under tension could be explained by dislocation glid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Under such conditions, the physical mechanism of plastic deformation is expected to be the thermally activated motion of dislocations past lattice obstacles, as it is for bulk samples of these materials, but with values of flow stress reflecting the special conditions that prevail in small-scale structures. This expectation was reflected in the early work of Flinn et al 4 and Volkert et al 8 on Al and Cu films, and it has been confirmed through direct observations by Kobrinsky and Thompson, 18 as noted earlier. The theory of thermally activated glide of dislocations in fcc metals has its origins in statistical mechanics, but its implementation in continuum plasticity theory is largely empirical.…”
Section: Plastic Rate Equationssupporting
confidence: 54%
See 2 more Smart Citations
“…Under such conditions, the physical mechanism of plastic deformation is expected to be the thermally activated motion of dislocations past lattice obstacles, as it is for bulk samples of these materials, but with values of flow stress reflecting the special conditions that prevail in small-scale structures. This expectation was reflected in the early work of Flinn et al 4 and Volkert et al 8 on Al and Cu films, and it has been confirmed through direct observations by Kobrinsky and Thompson, 18 as noted earlier. The theory of thermally activated glide of dislocations in fcc metals has its origins in statistical mechanics, but its implementation in continuum plasticity theory is largely empirical.…”
Section: Plastic Rate Equationssupporting
confidence: 54%
“…In this case, stress can be imposed on the film by changing the temperature of the system. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The constraint of the substrate implies that the generated thermal strain is essentially offset by the generation of some combination of elastic and plastic strain in the film. If is the equi-biaxial stress in the film, and p is the equi-biaxial plastic strain, then rates of change are related by /M ϩ p ϩ (␣ film Ϫ ␣ sub )Ṫ 0,…”
Section: Measuring Plastic Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating segment of all the curves follow approximately the same slope (M heating ) until initial yielding, indicating the elastic modulus is independent of ZnO concentration as would be expected in these dilute solutions. After the initial elastic portion of the heating curve, the stress slowly levels out as the temperature increases, indicating the start of plasticity brought on by diffusion-based creep, dislocation motion, grain growth, or phase transformations [37][38][39], most likely a mixture of multiple mechanisms depending on the stress and temperature state [40][41][42]. The stress at the onset of plasticity (r min ) is unique for each film and is indicative of the strength of the film, with increasing strength for increasing ZnO content.…”
Section: Wafer Curvaturementioning
confidence: 99%
“…Models taking into consideration of specific aspects of diffusional flow pertaining to the columnar grain structure have also been reported [57,72,[206][207][208]. The rate equations, in various formats with different levels of complexity, have been applied to investigate a wide variety of time-dependent mechanical response of polycrystalline blanket films bonded to stiff substrates [50,55,57,58,61,62,65,69,70,72,[209][210][211][212][213].…”
Section: Rate-dependent Behaviormentioning
confidence: 99%